Effects of pyrazinamide, probenecid, and benzbromarone on renal excretion of oxypurinol. Issue 9 (September 1991) - Yamamoto, T; Moriwaki, Y; Takahashi, S; Suda, M; Higashino, K
Abstract : The effects of pyrazinamide, probenecid, and benzbromarone on renal excretion of oxypurinol were investigated. Pyrazinamide decreased the mean (SEM) fractional clearance of oxypurinol from 19.2 (2.1) to 8.8 (1.5). Probenecid increased the fractional clearance of oxypurinol from 14.1 (3.5) to 24.8 (4.1). Benzbromarone increased the fractional clearance of oxypurinol from 15.6 (2.3) to 33.8 (2.8). These results suggest that oxypurinol may be secreted by 'an organic acid system' and that oxypurinol is reabsorbed at a putative postsecretory site of the renal tubules.